Anharmonic coupling, thermal transport and acoustic wave attenuation in cubic semiconductors and bismuth. (March 2020) - Markov, Maxime; Sjakste, Jelena; Vast, Nathalie; Perrin, Bernard; Paulatto, Lorenzo
Abstract: In this work we present our recent results of the ab initio calculations of anharmonic coupling in cubic semiconductors and bismuth. Our results allow us to explain the anomalous behavior of the attenuation of the longitudinal acoustic phonon in GaAs as a function of the phonon energy in the subterahertz domain, which shows a plateau between 0.6 and 1 THz at low temperatures. The plateau is explained by the competition between different phonon-phonon scattering processes such as Herring's mechanism, which dominates at low frequencies, saturates, and disappears at higher frequencies. We found an excellent agreement between measurements performed by some of us, and new ab initio calculations of third-order anharmonic processes. We predict that the same phenomenon should occur in other cubic semiconductors. In the case of bismuth, we discuss the occurrence of the hydrodynamic heat transport regime at low temperatures, in consistency with the experimental observations. Bismuth is one of the rare materials in which second sound has been experimentally observed. Our calculations predict the occurrence of the Poiseuille phonon flow in Bi between 1.5 K and 3.5 K for sample size of 3.86 mm and 9.06 mm, in consistency with the experimental observations. We will also discuss a Gedanken experiment allowing to assess the occurrence of the hydrodynamic regime in any bulk material.